Blindness after laryngectomy and bilateral neck dissection in a diabetic patient: case report - Mamede, Rui Celso Martins; Figueiredo, David Livingstone Alves; Mamede, Fabrício Villela [UNESP] (Associação Paulista de Medicina (APM), 2001)
CONTEXTO: O esvaziamento cervical que acompanha a ressecção da lesão primária no tratamento dos tumores malignos das vias aerodigestivas superiores possibilita o surgimento de complicações inerentes a ela ou ao prolongamento do tempo cirúrgico, aumentando os riscos para o paciente. Entre as complicações que podem ocorrer está a amaurose, de incidência rara. RELATO do CASO: Um paciente submetido a laringectomia total e esvaziamento cervical seletivo à esquerda e radical modificado à direita, que evoluiu com amaurose, provavelmente decorrente de hipotensão intra-operatória, com contribuição dos Diabetes Mellitus descompensado e trombose da veia jugular interna à direita. Discutem as possíveis causas, os fatores de risco e os cuidados que devem ser tomados para evitar essa rara, mas tão debilitante complicação.

CONTEXT: Neck dissection that accompanies resection of the primary lesion in malignant tumors of the upper aerodigestive tracts may cause complications inherent to the procedure or to prolongation of surgical time, increasing the risks for the patient. Among the complications that might occur is blindness, a rare complication with only 10 cases reported in the literature thus far. OBJECTIVE: To present the case of a diabetic patient submitted to total laryngectomy and modified and selective neck dissection that resulted in blindness. CASE REPORT: The authors report on a patient submitted to total laryngectomy and selective neck dissection on the left side, and modified radical neck dissection on the right, who developed blindness. This was probably due to intraoperative hypotension plus the contribution of decompensated diabetes mellitus and thrombosis of the internal jugular vein on the right side. The possible causes, risk factors and care to be taken to prevent this rare but highly debilitating complication are discussed.
Keywords: Amaurose; Esvaziamento Cervical; Complicações dos Esvaziamentos Cervicais; Complicações dos Diabetes Mellitus; Blindness; Neck dissection; Complications of neck dissection; Complications of Diabetes Mellitus